School Climate Among Transgender High School Students: An Exploration of School Connectedness, Perceived Safety, Bullying, and Absenteeism - Pampati, Sanjana (J Sch Nurs, 2018)
This study used self-administered survey data from seven high schools in Florida with a majority Black and/or Hispanic sample to examine transgender students’ perceptions and experiences related to school climate in comparison to cisgender students. Using propensity score matching, a matched analytic sample was created of transgender and cisgender students (n=542, including 186 transgender youth). Adjusted weighted logistic regression models indicated that transgender students were significantly more likely to report ever being bullied at school, being bullied in the past 3 months, and not going to school ≥3 days during the past 30 days. Transgender students were significantly less likely to report feeling safe at school and having positive perceptions of all five school connectedness items compared to cisgender students. Recent bullying experiences moderated the association between transgender status and past month absences. Findings can inform potential roles for school nurses in improving school climate for transgender youth.